2011
DOI: 10.1111/j.1365-2842.2011.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health complaints after removal of amalgam fillings

Abstract: SUMMARY The aim of the present study was to investigate whether removal of all amalgam fillings was associated with long-term changes in health complaints in a group of patients who attributed subjective health complaints to amalgam fillings. Patients previously examined at the Norwegian Dental Biomaterials Adverse Reaction Unit were included in the study and assigned to a treatment group (n = 20) and a reference group (n = 20). Participants in the treatment group had all amalgam fillings replaced with other r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
6
31
0
2
Order By: Relevance
“…Several studies have reported that patients experience improved health after amalgam removal (Lygre et al, 2005;Melchart et al, 2008;Nerdrum et al, 2004;Sjursen et al, 2011). This has also been described in the qualitative studies performed within this field (Jones, 2004;Stahlnacke & Soderfeldt, 2013).…”
Section: T T Sjursen Et Almentioning
confidence: 75%
See 2 more Smart Citations
“…Several studies have reported that patients experience improved health after amalgam removal (Lygre et al, 2005;Melchart et al, 2008;Nerdrum et al, 2004;Sjursen et al, 2011). This has also been described in the qualitative studies performed within this field (Jones, 2004;Stahlnacke & Soderfeldt, 2013).…”
Section: T T Sjursen Et Almentioning
confidence: 75%
“…Studies investigating changes in general health complaints after removal of amalgam fillings have found reductions in health complaints (Lygre et al, 2005;Melchart et al, 2008;Nerdrum et al, 2004;Sjursen et al, 2011), but not to the levels found in the general population (Lygre et al, 2005;Nerdrum et al, 2004). The observed reductions in health complaints might be interpreted as effects of patients being seen and heard, improved dental conditions, the natural variation in the course of the complaints, reduced exposure to mercury, as well as placebo effect and discontinued nocebo effect (Melchart et al, 2008;Nerdrum et al, 2004;Sjursen et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CAM is also frequently used by patients with health complaints related to amalgam [9,[13][14][15][16]. In recent studies, the most commonly reported CAM modalities for this patient group were dietary supplements/vitamins (58-92 %) [9,14,15,17], homeopathy (17-26 %) [9,13,14], acupuncture (13-28 %) [2,9,14,16] and chiropractic (18-21 %) [14,16]. In Norway the most commonly reported CAM modalities used for amalgam-related health complaints are dietary supplements, acupuncture and homeopathy (65 %, 28 % and 26 % respectively) [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the most commonly reported CAM modalities for this patient group were dietary supplements/vitamins (58-92 %) [9,14,15,17], homeopathy (17-26 %) [9,13,14], acupuncture (13-28 %) [2,9,14,16] and chiropractic (18-21 %) [14,16]. In Norway the most commonly reported CAM modalities used for amalgam-related health complaints are dietary supplements, acupuncture and homeopathy (65 %, 28 % and 26 % respectively) [9,17]. The literature has revealed that the prevalence and associations for use of CAM differs between men and women with regard to several socio demographic variables [18][19][20][21][22][23] and underline the importance of gender-specific analyses [24].…”
Section: Introductionmentioning
confidence: 99%